Feasibility study of a non-invasive eye fixation and monitoring device using a right-angle prism mirror for intensity-modulated radiotherapy for choroidal melanoma. (3rd November 2016) - Inoue, Toshihiko; Masai, Norihisa; Shiomi, Hiroya; Oh, Ryoong-Jin; Uemoto, Kenji; Hashida, Noriyasu
Abstract: We aimed to describe the feasibility and efficacy of a novel non-invasive fixation and monitoring (F-M) device for the eyeballs (which uses a right-angle prism mirror as the optic axis guide) in three consecutive patients with choroidal melanoma who were treated with intensity-modulated radiotherapy (IMRT). The device consists of an immobilization shell, a right-angle prism mirror, a high magnification optical zoom video camera, a guide lamp, a digital voice recorder, a personal computer, and a National Television System Committee standard analog video cable. Using the right-angle prism mirror, the antero–posterior axis was determined coincident with the optic axis connecting the centers of the cornea and pupil. The axis was then connected to the guide light and video camera installed on the couch top on the distal side. Repositioning accuracy improved using this method. Furthermore, the positional error of the lens was markedly reduced from ±1.16, ±1.68 and ±1.11 mm to ±0.23, ±0.58 and ±0.26 mm in the horizontal direction, and from ±1.50, ±1.03 and ±0.48 mm to ±0.29, ±0.30 and ±0.24 mm in the vertical direction (Patient #1, #2 and #3, respectively). Accordingly, the F-M device method decreased the planning target volume size and improved the dose–volume histogram parameters of the organ-at-risk via IMRT inverse planning. Importantly, the treatment method was well tolerated.